Penggunaan Model PBL untuk Meningkatkan Hasil Belajar Siswa pada Materi Simbol dan Nilai-Nilai Pancasila di SDN Sendangmulyo 02 Semarang - Hamidatun Noor; Fenny Roshayanti; Husni Wakhyudin (Journal on Education, 2023)
This study aims to determine the effect of the PBL model to improve student learning outcomes in grade 1 at SDN Sendangmulyo 02 Semarang. This type of research is quantitative. The population in this study amounted to 28 students. The research design used a quasi-experimental design for grade 1 students. The research data were analyzed by using the effectiveness test on the application of the Problem Based Learning (PBL) learning method using the normality test, t test, homogeneity and n gain with the help of the SPSS version 26 program. The test results, significant t test pretest 0.921 > 0.05, for the homogeneity test shows that the score is 0.92 > 0.05 then Ho is accepted. The t test obtained a tcount of 8.858 and a significance value of 0.000. The value of tcount > ttable (8.858 > 1.697) and n gain n gain score 0.6 is in the medium category, because ≥ 0.3 and ≤ 0.7. Students respond to the use of PBL very well, because learning is not boring and becomes more meaningful. So it can be concluded that the PBL learning model is effective for grade 1 student learning outcomes in material symbols and values ​​of Pancasila.